Survey of Volleyball Underhand Serve and Underarm of Students at SMP Negeri 1 Siak Hulu - Mimi Yulianti; Rices Jatra; Leni Apriani; Rahma Wati; Subagyo Subagyo; Sujarwo Sujarwo (UNIB Press, 2024)
This research is descriptive research, namely only describing the bottom serving and bottom passing abilities of Class VIII Students of SMP Negeri 1 Siak Hulu in 2023/2024. The population of this study was male students in class VII at SMP Negeri 1 Siak Hulu. In the 2023/2024 academic year, the aim was to determine the lower serving and lower passing abilities of volleyball students at SMP Negeri 1 Siak Hulu. The population in this study were students of SMP Negeri 1 Siak Hulu who had the same age level, namely 12-13 years with a sample size of 30 students and sampling using random sampling, namely a research method using surveys then data collection techniques using tests and measurements. The research results showed that the service ability of students at SMP Negeri 1 Siak Hulu was in the poor category, and The lower passing ability of students at SMP Negeri 1 Siak Hulu obtained the lower passing test results in the sufficient category 37%.